Unclaimed medication by patients that have been filled according to prescriptions in Pharmacy Out Patient Department - Anwar, Azreen Syafiqeen; Anwar, Siti Nur Afzan; Ariffin @ Azmi, Nur Izyan Liyana (2010)
Prescriptions that ae ordered by physicians but not collected by patients represent a potential quality disimprovement opportunity in health systems. Prescriptions that are filled but remain unclaimed are the marker for patients' non-compliance with their medication regimens. Therefore, a research of uncollected prescriptions was done in Out Patient Department of Pharmacy in HRPZ II to determine the trend in late collection of prescriptions and to determine the reasons of patients for non-collection and late collection. This research also determines the effects of unclaimed prescriptions on OPD Pharmacy's staff workload. Besides, our aim is also to find relevant suggestion for improvement plan. We focus on two methods to gain the data. The first method is; data collection form, where it is carried out for the period of 4 months starting on 4 October 2009- 24 January 2010. Another method is by setting up a questionnaires based on our research objectives, that is to identify who (staff or patient), what types of medications that are frequently uncollected, reasons for non-collection and late collection, and also the waiting time. These questionnaires are distributed randomly among patients of OPD Pharmacy by the dispensers. Data from selected questions of the questionnaires are estimated using Microsoft Excel. As my research showed that an average of prescriptions per day is wasted during the research period due to annulment. 10 prescriptions per day were not collected on time within 24 hour period after it arrived at OPD Pharmacy. From data collection form, out of this number, 73% of prescriptions owners are patients and 27% are HRPZ II staff. Paracetamol is the most popular prescribed medicines in those prescriptions. 60% of respondents in survey have admitted to leave prescriptions uncollected or late-collection or both, have their own reasons. The uncollected prescription affects patients' compliance and staff workload therefore necessary improvement changes in work system are beneficial to reduce the problem of uncollected prescription.